Prescribed burning effectively maintains threatened species in semi‐natural grasslands on lava flows - Airi A. Asada; Atsushi Ohwaki; Yuki A. Yaida; Fuma Kawakami; Masaki Masuda; Atushi Ushimaru (Plants, People, Planet)
Societal Impact Statement Prescribed burning shows promise for managing certain grassland types, but relying solely on it often reduces plant diversity, including threatened species. In Japanese dry grasslands established on volcanic ejecta, we explored conditions under which burning maintains high diversity. Lava grasslands, especially those on young lava flows with hard, shallow, and acidic soil and high rock and stone cover, harbored the most diverse plants, including threatened species. Burning helps prevent forest encroachment, efficiently maintaining species‐rich grasslands on lava flows. We recommend this approach to land managers for maintaining grasslands and conserving threatened plants, particularly in shallow, acidic soil conditions. Summary Prescribed burning can be an effective and efficient method for managing large areas of grasslands, particularly in face of global increases in grassland abandonment. However, relying solely on regular burning often leads to declines in diversity of grassland plants including threatened species in Eurasian countries. Therefore, investigating conditions under which prescribed burning effectively conserves threatened species is highly important. We hypothesized that under specific soil physicochemical conditions, even burning‐only management can maintain high threatened species diversity. To test the hypothesis, we compared soil physicochemical properties and vegetation among burning‐managed grasslands on different volcanic bedrocks (young/old lava and scoria) in Nashigahara, Yamanashi, Japan. We quantitatively investigated how bedrock, soil, and vegetation properties affected diversity of plants, including threatened species. We found the highest plant diversity in young lava grasslands, which were characterized by hard and shallow soil and high rock and stone cover, than old lava and young/old scoria grasslands. Meanwhile, soil nutrients (N, P, K, Ca, and Mg) did not vary among bedrock types and had no significant effects on plant diversity. In young lava grasslands, shallow soil, low soil pH, and resulting low vegetation height caused high threatened species diversity, supporting the hypothesis. Mature vegetation on lava flows often comprises forests worldwide. Nonetheless, our findings suggest that prescribed burning successfully suppresses tree dominance and promotes the establishment of highly species‐rich grasslands on lava flows. We propose that prescribed burning can effectively conserve threatened species in semi‐natural grasslands established under specific soil environments, such as those on lava flows.